Left ventricular twist mechanics and its relation with aortic stiffness in chronic kidney disease patients without overt cardiovascular disease. Issue 1 (December 2015) - Sulemane, Samir; Panoulas, Vasileios; Konstantinou, Klio; Bratsas, Athanasios; Tam, Frederick; Brown, Edwina; Nihoyannopoulos, Petros
Abstract Background Recent studies hypothesized left ventricular (LV) twist as a potential biomarker for evaluation of sub clinical myocardial disease, however its relationship with aortic stiffness has yet to be investigated. Chronic kidney disease (CKD) has been identified as a risk factor for both myocardial and arterial disease. As such we sought to explore the relationship between aortic stiffness and LV twist in CKD patients without known cardiovascular disease (CVD). Methods In this prospective, observational study we enrolled 106 CKD patients (Stages 1 to 5) with normal LVEF as assessed by conventional echocardiography. Aortic stiffness was measured using aortic pulse wave velocity (aPWV). We defined increased aPWV as ≥10 m/s. LV Twist was measured using two-dimensional speckle tracking echocardiography. Results Patients with increased aPWV had higher LV twist (p = 0.002) but similar LVEF (p = 0.486). Aortic PWV correlated crudely with age (p < 0.001), the presence of diabetes (p < 0.001), hypertension (p < 0.001), eGFR (p < 0.001), LVMI (p = 0.01), e/e' (p < 0.001) and LV twist (p = 0.003). In multivariable analyses after adjusting for age, gender, cardiovascular risk factors and hypertensive medication, aPWV was independently associated with LV twist (β = 0.163, p = 0.025). Conclusions Aortic stiffness independently associates with LV Twist in asymptomatic CKD patients. These findings suggest a close interaction between LV twist mechanics and arterial remodeling even before CVD becomes clinically relevant.